The Flying Bicycles: Cycling Along the German German Border - König, Constanze (Jigd, 2007)
Duration: 01:32:00 A road documentary in which members of AK Grenzsprenger study camp take a bike tour along the German-German border to revisit the borderline that once split the country in half.